Beyond Efficacy: How Self-Esteem and Guilt Drive Participation in Tourism Boycotts - Minkyung Park; Hochan Jang (Tourism and Hospitality)
While tourism boycotts can have a considerable economic impact on a target entity, critics often question their effectiveness in changing the target entity’s behavior, particularly in international contexts. Despite these challenges, tourism boycotts have increased over time. This study explores the dynamics of tourism boycotts amid international political conflicts and investigates the motivations behind consumer participation. During an ongoing national boycott in South Korea, we conducted an online survey with a nationally representative adult panel, gathering 962 responses for analysis. Our findings reveal that tourism boycott participants—primarily women, older individuals, those with higher education and income, and the progressive—resemble consumer boycott participants in Europe and the U.S. While perceived efficacy (instrumental motivation) is often emphasized in consumer boycotts as a key variable for participation, our study suggests that tourism boycotts are primarily driven by expressive motivations, such as self-esteem and guilt, rather than a mix of instrumental and expressive factors. This suggests that consumers engage in tourism boycotts not necessarily to achieve tangible outcomes, but to express personal or ethical values, highlighting a distinctive nature of tourism boycotts in the landscape of consumer activism.